Synthesis, Biological Activity and QSAR Studies of Organotin(IV) and Organosilicon(IV) Complexes. Issue 15 (17th April 2019) - Devi, Jai; Devi, Suman; Yadav, Jyoti; Kumar, Ashwani
Abstract: A panel of penta‐coordinated, neutral organotin(IV) and organosilicon(IV) complexes of newly designed Schiff bases: 4‐(2‐hydroxymethyl‐phenylimino)‐2‐methyl‐4H‐pyran‐3‐ol (H2 L 1 ) and 4‐(benzothiazol‐2‐ylimino)‐2‐methyl‐4H‐pyran‐3‐ol (HL 2 ) were synthesized and characterized using elemental analysis, spectral studies (UV/Vis, IR, 1 H, 13 C, 29 Si, 119 Sn NMR and Fluorescence) and thermal technique. Spectral studies conferred that the Schiff base act as bi/tridentate and form the penta coordinated geometry with oxygen and nitrogen donor atom (NO/NOO). The compounds were screened for in vitro antimicrobial activity using twofold serial dilution method against Gram‐positive bacteria ( Staphylococcus aureus, Bacillus cereus ), Gram‐negative bacteria ( Escherichia coli, Klebsiella pneumoniae ) and fungi ( Aspergillus niger, Candida albicans ). The antimicrobial study exposed good activity with tri‐ and di‐phenyl derivatives exhibiting excellent biological activity. Compounds5, 6, 10, 13, 14, 17 and18 displayed better activity than the standard drugs. Quantitative structure activity relationship involves correlation of biological activity with the structural properties of the compounds using statistical means. Abstract : Penta‐coordinated potent complexes of silicon and tin were synthesized and their structure‐ activity relationship described Bu3 SnL 2 and Ph3 SnL 2 are found to be biologically potential antimicrobial agent.